EFFICIENCY OF FINISH FACE MILLING OF HARDENED STEELS WITH POLYCRYSTALLINE CUBIC BORON NITRIDE (PCBN) TOOLS - KOVALENKO, YANA; MELNYCHUK, PETRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents the results of a study on the efficiency of the finish face milling process of hardened steel 4X5MFS using cutting inserts made of polycrystalline cubic boron nitride (PCBN) of the BL and BH groups, both uncoated and with wear-resistant coatings. Finish face milling of hardened steels is one of the key technological processes in modern mechanical engineering, particularly in the manufacturing of dies, molds, cutting, and forming tools. The application of PCBN as a tool material significantly enhances machining efficiency by ensuring process stability and achieving a high-quality machined surface. The study investigates the effect of the geometric parameters of the cutting insert, specifically negative chamfer angles of -20° and -25°, on the formation of the microrelief of the surface after face milling of hardened steel 4X5MFS. Experimental studies showed that machining with an insert having a -25° chamfer (DBS900 cutting insert) resulted in a lower surface roughness (Ra < 0.3 µm) compared to machining with a -20° chamfer (CBN200 cutting insert). This effect is attributed to a more uniform load distribution, reduced microchipping, and a more stable cutting process. The effect of the feed rate on the quality of the machined hardened steel 4X5MFS surface after face milling with PCBN tools was also examined. It was found that increasing the feed rate from 0.1 mm/tooth to 0.125 mm/tooth resulted in a decrease in surface roughness (Ra = 0.3 µm, Ra = 0.34 µm). This phenomenon is explained by the fact that at lower feed rates, the chip thickness may approach the minimum chip thickness, leading to a sliding effect of the tool on the material instead of a clean cut, which causes micro-deformations and worsens surface roughness. Additionally, the study analyzed the formation of residual stresses in the surface layer, particularly the influence of the TiSiN coating on residual stress formation. The results showed that uncoated tools generate tensile residual stresses, whereas TiSiN-coated tools create compressive residual stresses. This effect is attributed to the lower friction coefficient of the coating, which reduces local heating of the surface and minimizes plastic deformations, thereby promoting the formation of compressive stresses that enhance the durability of the component. The obtained results confirm the effectiveness of using PCBN cutting inserts for finish face milling of hardened steel 4X5MFS. The application of cutting inserts with a -25° chamfer and TiSiN coating allows for achieving lower surface roughness and forming favorable compressive residual stresses, which improves the operational reliability and longevity of the machined components. Using polynomial regression, a correlation coefficient of 0.95 was determined in the mathematical model of the face milling process. In particular, the influence of cutting parameters on the predicted surface roughness values was established, and the obtained mathematical predictions were compared with the experimental data.